Uji Efektivitas Antiinflamasi Ekstrak Daun Jamblang (Syzygium cumini L.) terhadap Mencit (Mus musculus L.) yang diinduksi Karagenan - Zunnita, Oktaviana; Moerfiah, Moerfiah; Auliya, Risa (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2024)
Inflammation is a protective process against tissue injury caused by infection, trauma, or chemicals. The mechanism of inflammation starts from a stimulus that will cause cell damage, these cells will release several phospholipids, one of which is arachidonic acid. Free arachidonic acid will be activated by cyclooxygenase and lipoxygenase enzymes. This enzyme converts arachidonic acid into an unstable form which is further metabolized to leukotrienes, prostaglandins, prostacyclin, and thromboxane. One of the natural medicines used as an inflammatory treatment is jamblang leaf, because there are flavonoids that can inhibit cyclooxygenase and lipoxygenase enzymes. This study aims to determine the anti-inflammatory effect and the best dose of jamblang leaf extract. The method used was 1% carrageenan induction and a digital plethysmometer to measure the volume of inflammation on the soles of the test animals' feet. The test animals used were 25 mice divided into 5 treatment groups, each group consisting of 5 mice. The treatment group consisted of: negative control of 1% Na-CMC, positive control of Diclofenac Sodium 0.182 mg/20 g BW, dose 1 of jamblang leaf extract 10 mg/20 g BW, dose 2: 15 mg/20 g BW and dose 3: 20 mg/kg 20 g BB. The results showed that all doses of jamblang leaf extract had an anti-inflammatory effect and dose 3 was the best dose that reduced the volume of inflammation.